Domestic Textile Production in Colonial Quebec, 1608-1840 - Ruddel, David Thiery (Material Culture Review, 1990)
In the early twentieth century, ethnographers and economic historians showed an interest in a variety of themes including gender roles and the early evolution of textile production. Most work since then has been ethnographically and museologically based, drawing on historical sources, such as household in-ventories and marriage contracts but also on artifacts, a largely unknown phenomenon to most historians. While museum curators and specialists in Quebec ethnography have emphasized the material remains of household cloth and the various steps in its fabrication, most economic historians have been primarily interested in agricultural and industrial productivity. Colonial historians, for example, use information about wool, flax and hemp in their arguments concerning self-sufficiency and commercial agriculture and rarely explore the ways in which households were organized to meet their daily needs. These historians have, therefore, neglected the role offemale labour in the countryside, as well as women's participation in the rural market-place. Although woman's work and clothing are also within the sphere of social history, the lack of sources and the fact that these subjects are usually treated within larger contexts has meant that cloth making and use have yet to receive the attention they deserve. After surveying the historiography related to home-made textiles, the author discusses the role of the domestic production of fabric in Quebec, as well as the subject of gender in the making of household cloth. Résumé Au début du XXe siècle, les ethnographes et les historiens de l'économie se sont intéressés à une grande variété de thèmes, y compris les rôles sexuels et l'évolution de la production textile au début de la colonie. La plupart des travaux des dernières décennies s'inscrivent dans une démarche ethnographique etmuséo-logique, et reposent sur une documentation d'époque, comme des inventaires de ménages et des contrats de mariage, mais aussi sur des artefacts, une source largement inexploitée par la majorité des historiens. Tandis que les conservateurs de musées et les spécialistes de l'ethnographie québécoise ont mis l'accent sur les vestiges matériels des textiles domestiques et les diverses étapes de leur fabrication, la plupart des historiens de l'économie se sont surtout intéressés à la productivité agricole et industrielle. Les historiens de l'époque coloniale, par exemple, exploitent les données accessibles concernant la laine, le lin et le chanvre dans leurs exposés sur l'autosuf-fisance des premiers colons et l'agriculture commerciale, mais ils étudient rarement les modes d'organisation familiale qui permettaient aux ménages de subvenir à leurs besoins courants. Le rôle de la main-d'œuvre féminine à la campagne, de même que la participation des femmes à l'économie de marché en milieu rural, sont par conséquent des aspects que ces historiens ont négligés. Même si le travail des femmes et l'habillement ont leur place dans l'histoire sociale, l'absence de sources et le fait que l'on traite ordinairement de ces sujets dans des contextes plus larges ont malheureusement mis en veilleuse l'étude de la production et de l'utilisation des étoffes. Après un survol de l'historiographie consacrée aux textiles de fabrication domestique, l'auteur examine le rôle de la production familiale du tissu au Québec, ainsi que les aspects sexués de la fabrication d'étoffes pour la famille.